Respuestas

2013-08-21T02:19:59+02:00
7 · 3 + [ 6 + 2 · (23 : 4 + 3 · 2) – 7 · ] + 9 : 3 = = 7 · 3 + [ 6 + 2 · (8 : 4 + 3 · 2) – 7 · 2 ] + 9 : 3 = = 21 + [ 6 + 2 · (2+ 6) – 14] +3 = = 21 + ( 6 + 2 · 8 – 14) +3 = = 21 + ( 6 + 16 – 14) + 3 = = 21 + 8 + 3 = 32


14 − {7 + 4 · 3 - [(-2)2 · 2 - 6)]}+ (22 + 6 - 5 · 3) + 3 - (5 - 23 : 2) = 14 − [7 + 4 · 3 -(4 · 2 - 6)] + (4 + 6 - 5 · 3) + 3 - (5 - 8 : 2) = 14 − [7 +12 -(8 - 6)] + (4 + 6 - 15) + 3 - (5 - 4) = 14 − (7 +12 -2) + (-5) + 3 - (1) = 14 − (17) + (-5) + 3 - (1) = 14 − 17 - 5 + 3 - 1 = −6